INNOVATIVE DOMINANCE OF UNIVERSITY SCIENCE - Vladislav E. Kuleshov; Vasiliy A. Zykov; Olga A. Volkova (Высшее образование в России)
The article reveals the strategy of innovative development of USTU. By means of conceptual metaphor, «The Planet University», USTU is presented as model of innovative economy. Process of formation of innovative territorial cluster «Oil and gas technologies», and business incubator of USTU «Ukhta - The Homeland of the First Russian Oil » is described. The initial unit (the low pole) of all the innovation lines is presented by the research schools(14) associated with the priority development areas. The network of innovative and scientific and industrial centres, research institutes form the innovation zone (equator) around «The Planet University». The upper pole (manufacturing of a competitive product) is formed conjointly by the university complex, cluster, and technopark.